PENGARUH DAN RELEVANSI GUSJIGANG BAGI PERADABAN ISLAM DI KUDUS - Nur, Dany Miftah; Farohi, Ahmad (IJTIMAIYA: Journal of Social Science and Teaching, 2019)
Sayyid Ja'far Sodiq or known as Sunan Kudus is a figure who has an important role in the entry of Islam in Kudus. The multicultural Holy Society has a unique typology in morals, science and economics, known as "Gusjigang", Bagus-having good behavior), Ji (Ngaji-good at reciting the Qur'an) and Gang (Dagang —good at trading). The identity crisis brings human consciousness to explore the wealth, wisdom and excellence contained in local culture, build and strengthen the identity and pride of the nation. Modernization or more accurately said as Westernization on the one hand is able to achieve rapid progress, but on the other hand it fails to achieve prosperity for nature and humans. This study reveals the influence and relevance of Gusjigang from Kanjeng Sunan Kudus in moderating Islam in Kudus in life with a unique format and typology that is able to become a new concept for the development of morals, science and economics (trade) so as to create a prosperous and prosperous society.